The Impact of Digital Banking Transformation on Financial Performance and Risk Reduction in a Sample of Iraqi Commercial Banks for the Period 2020-2025 - Yasir Majeed Dahdooh (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The research aims to analysis effect Transformation digital banker on performance financial and reduction risks in sample from banks commercial Iraqi, It is : Bank Al-Mansur, bank via Iraq, bank the East Middle, bank Mosul, bank Investment, and bank Erbil, That's during The period (2020–2025) . Acquired the topic importance Increasing in shadow Orientation Global about digitization Finance And adopt Technologies Modern in presentation Services Banking . Approved . Search on Curriculum Descriptive Analytical, from during Use Data Finance extracted from Reports Annual For banks place the study, Please on Data Bank Central Iraqi . And it was measurement Transformation digital via group from Indicators, From it spread Services Banking Electronic, and level Investment in technology Information and size Transactions Digital . In when It was completed measurement Performance Financial Using Indicators Profitability And efficiency, like Return on Assets ( ROA ) and Return on rights Ownership ( ROE ) , As for Risks Banking Lost It was completed measuring it from during Indicators risks Credit Liquidity And operation . Connection . Search to presence relationship The indication Statistics between Transformation digital And improved Performance Financial For banks, Please on turn in discount some Types Risks, Especially Risks Operational . As well . Showed Results presence disparity between banks in degree Benefit from Transformation Digital, He returns to difference levels Structure Infrastructure Technology and strategies Digital Approved . Recommended . Search Necessity Strengthening Investment in Technologies Digital, and development Structure Infrastructure Banking, And adopt Strategies Digital Integrated, In what Contributes in to improve Performance Financial and reduce Risks, and strengthening ability competitiveness For banks Iraqi in the environment Banking Modern.